Driving through a pandemic: A study of speeding and phone use while driving during COVID-19 restrictions. (5th November 2021) - Truelove, Verity; Watson-Brown, Natalie; Parker, Emily; Freeman, James; Davey, Jeremy
Abstract: Objective: In response to the COVID-19 pandemic, restrictions were implemented, however, data indicates road crash rates have not decreased proportionately to the decline in traffic density. This study explored how speeding and phone use while driving (road behaviors associated with a high crash risk) changed as a result of COVID-19 restrictions in Queensland. Methods: Two cross-sectional studies were conducted in Queensland, Australia to examine self-reported changes in speeding and phone use while driving before, during and after the easing of restrictions (while also considering exposure to the road and driving location). Study 1 ( n  = 351) was conducted between 12 May and 12 June 2020, when the majority of COVID-19 restrictions were enforced. Study 2 ( n  = 427) was conducted between 24 June and 12 August 2020, when restrictions were easing. Results: The findings indicated, overall, self-reported speeding and phone use significantly decreased during restrictions (likely due to reduced travel), but not for those who continued to drive regularly. There was an additional, significant self-reported decrease in phone use while driving after restrictions were eased when compared to engagement during restrictions, which may (in part) be due to the simultaneous introduction of roadside mobile phone detection cameras. Conclusion: These findings highlight the importance of visible deterrence and provide a glimpse of possible consequences if there is a more sustained reduction in policing presence on roads.